National and international policies for tropical rain forest conservation: a quantitative analysis for Cameroon - Rainer Thiele; Manfred Wiebelt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
This paper provides a numerical general equilibrium assessment of policies to reduce tropical deforestation in Cameroon. Market failure - mainly in the form of national and international externalities - and policy failures - such as highly distorted product markets - are identified as major sources of overexploitation. The ecological effects of deforestation control are shown to depend crucially upon its impact on land use patterns whereas its efficiency effects hinge on the manner in which a specified set-aside target is achieved. If the international community wants to ensure a higher level of protection of these forests, and to do so within a market-based system, the provision of conditional financial resources is necessary.
Keywords: Q2; D58; 330; Forstpolitik; Umweltpolitik; Simulation; Allgemeines Gleichgewicht; Kamerun; Tropen